Pengaruh Organizational Citizenship Behavior, Beban Kerja dan Job Description terhadap Kinerja Karyawan - Tresiana, Ni Putu Mia; Yudy Wijaya, Putu; Alit Suputra, Gusti (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The purpose of this study is to determine the effect of organizational citizenship behavior, workload and job description on employee performance. The location of this study was carried out on CV. Sustainable Agro Tani in Denpasar City. The sample used in this study was 31 respondents. The data analysis techniques used are classical Assumption Test, Multiple Linear Regression, Coefficient of Determination, t Test and f Test. Based on the results of the study, it can be seen that organizational citizenship behavior does not have a significant effect on employee performance, workload has a negative and insignificant effect on employee performance, job description has a positive and significant effect on employee performance and simultaneously organizational citizenship behavior, workload and job description have a positive and significant effect on employee performance. The magnitude of the influence of the independent variable on employee performance is 30.9%. The advice in this study is CV employees. Agro Tani Lestari in Denpasar City is expected to help fellow colleagues to support productivity, CV leader. Agro Tani Lestari in Denpasar City does not provide too much additional work suddenly so that employees are not burdened in working and it is expected that CV. Agro Tani Lestari is able to make improvements to work that needs to be improved.